Juridical Review of Criminal Sanctions Against Perpetrators of Intellectual Property Rights Violations - Fransisca Dewi Zion; Evita Isretno Israhadi; Ahmad Redi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Copyright is the exclusive right of the Creator or Copyright Holder to regulate the use of the results of casting specific ideas or information. Copyright applies to various types of works of art or copyrighted works. With the existence of Law Number 28 of 2014 concerning Copyright, it is hoped that it will facilitate proof in copyright disputes, especially in works of art, as well as the originality of ideas, content, and digital products.